For the record - Polak, Monique (Owlkids Books, 2022)
When her divorced mother--seeking to gain sole custody--asks her to compile a list of bad things her father does while she and her little sister, Bea, are staying with him, twelve-year-old Justine goes along with it, writing in her secret notebook. However, when the court case draws near, Justine finds herself writing a complete lie just to help her mother's case. Now Justine has to wonder about her mother's behavior, and her own, and must find the courage to tell the truth.